Citizenship Education Curriculum in the Industrial Revolution Era 4.0 - Nugraha, Yogi; Firmansyah, Yudi; Ramadhan, Nabilah (International Journal of Psychosocial Rehabilitation, 2020)
General objective of this study was to determine the digital-based Civic Education curriculum in Indonesia in the era of industrial revolution 4.0 The method used in this research is studi libraries or also known as the study of texts. A literature study is used to understand deeply and comprehensively about the curriculum of civic education in the industrial revolution era 4.0. The results obtained showed that the civic education curricula have Identics with citizen rights and obligations, democracy, human rights, nationalism, geopolitical and geostrategic. Civic education curriculum needs to renew the system of learning and teaching model with the times. In practical results of this study can be used as reference material citizensip education further research writing. Then the results of this study can be used as study materials about the course curriculum citizenship education in the era of industrial revolution 4.0.